PENINGKATAN HASIL BELAJAR MATERI KORDINAT KARTESIUS DENGAN PENERAPAN PEMBELAJARAN STUDENT TEAMS ACHIEVMENT DEVITION - RENI ASTUTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This research is a Classroom Action Research which was carried out with the aim of describing the implementation of learning and knowing the improvement of learning outcomes in Cartesian coordinates material with the application of Student Teams Achievment Devition (STAD) learning. The research was conducted in two cycles, the first cycle consisted of 3 meetings and the second cycle consisted of 2 meetings. The research subjects were students of class VIII D MTsN 1 Bantul in the odd semester of the 2018/2019 academic year, which consisted of 16 girls and 15 boys. The data collection methods are in the form of observation, documentation, and tests. The data obtained were then processed by qualitative descriptive analysis. The results showed that the activity aspect increased from pre-cycle by 58.07%, to 80.68% in the first cycle and in the second cycle it reached 100%. In the aspect of learning achievement, the average pre-cycle score reached 63.4, in the first cycle it reached 74.2 and in the second cycle it reached 88.1. While the percentage of completeness also increased, from 41.94% in the pre-cycle to 70% in the first cycle and 83.87% in the second cycle. Based on the data, it can be concluded that the application of Student Teams Achievment Devition learning on the Cartesian coordinates material can improve mathematics learning outcomes for class VIII D MTsN 1 Bantul odd semesters for the 2018/2019 academic year. ABSTRAKPenelitian ini merupakan Penelitian Tindakan Kelas yang dilaksanakan dengan tujuan untuk mendeskripsikan pelaksanaan pembelajaran dan mengetahui peningkatan hasil belajar pada materi koordinat kartesius dengan penerapan pembelajaran Studen Teams Achievment Devition (STAD). Penelitian dilakukan dalam dua siklus, siklus pertama terdiri dari 3 pertemuan dan siklus kedua terdiri 2 pertemuan. Subjek penelitian adalah siswa kelas VIII D MTsN 1 Bantul semester gasal Tahun Pelajaran 2018/2019 yang terdiri dari 16 perempuan dan 15 laki-laki. Adapun metode pengumpulan data berupa pengamatan, dokumentasi, dan tes. Data yang didapat selanjutnya diolah dengan analisis deskripsi kualitatif. Hasil penelitian menunjukkan bahwa aspek keaktifan mengalami kenaikan dari pra siklus sebesar 58,07%, menjadi 80,68% pada siklus I dan pada siklus II mencapai 100%. Pada aspek prestasi belajar nilai rata-rata pra siklus mencapai 63,4, pada siklus I mencapai 74,2 dan pada siklus II mencapai 88,1. Sedangkan persentase ketuntasan juga mengalami kenaikan, dari 41,94 % pada pra siklus menjadi 70 % pada siklus I dan 83,87 % pada siklus II. Berdasar data dapat disimpulkan bahwa penerapan pembelajaran Studen Teams Achievment Devition pada materi koordinat kartesius dapat meningkatkan hasil belajar matematika siswa kelas VIII D MTsN 1 Bantul semester gasal Tahun Pelajaran 2018/2019.